THE EFFECT OF FINANCIAL DISTRESS AND SALES GROWTH ON COMPANY VALUE(A STUDY OF TRANSPORTATION & LOGISTICS COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE FROM 2020 TO 2024) - Al Ghifari Ramadan; Byandra Destianingrum; Selvia Rahma Yunita; Linawati (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
This study aims to determine the effect of financial distress and sales growth on firm value in transportation and logistics sector companies listed on the Indonesia Stock Exchange during the 2020-2024 period. The sampling technique was carried out using the purposive sampling method, so that 10 out of 39 companies in the sector were found that were in accordance with the criteria as samples. This number is then multiplied by the five-year research period, so that the total data obtained amounted to 50 observations. The data processing and testing process is carried out using EViews version 10 software which goes through several stages, namely descriptive statistical test, model selection test, classical assumption test, multiple linear analysis test, determination coefficient test (adjusted R2), partial test, and simultaneous test. The test results in this study show that financial distress has an effect on firm value, while sales growth has no effect on firm value. However, simultaneously, financial distress and sales growth have been proven to have an effect on firm value.